Analisis Kekuatan Struktur Bangunan Hotel Berdasarkan Respon Spektrum Terhadap Gaya Gempa di Kepulauan Riau Kota Batam Berdasarkan SNI 1726:2019 - Thohirin Thohirin; Pujiono T; Hardayani Haruno (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The dynamic development of Palembang City has resulted in increased traffic density on various road corridors, including Jalan Pangkalan in the Sako Baru area. This study aims to analyze the performance of Jalan Pangkalan in handling existing traffic flow and provide management recommendations based on the latest standards. The research method applied is quantitative analysis by conducting traffic volume, speed, and road geometry surveys. Primary data was obtained through direct field surveys to determine daily traffic volume, vehicle composition, and road geometric conditions Road performance evaluation was conducted using the Indonesian Road Capacity Guidelines (PKJI) 2023, which is the latest standard in road performance assessment in Indonesia. The study results show that Jalan Pangkalan faces varying service levels at certain periods. Based on analysis using PKJI 2023, road capacity values, degree of saturation (DS), and level of service (LOS) were obtained for that road segment. Maximum traffic volume occurs during morning and evening rush hours with vehicle composition dominated by motorcycles and light vehicles The road service level indicates conditions that require special attention, especially during peak hours where the degree of saturation approaches or exceeds optimal limits. This situation indicates the need for interventions to improve road performance so it can serve traffic flow better. The proposed recommendations include traffic management improvements, road geometric optimization, and implementation of traffic engineering appropriate to existing conditions. This research is expected to provide input for local government in policy-making related to transportation management in Palembang City.